Effect of asymmetry in the restoring force of the click mechanism in insect flight - Abolfathi, Ali; Changizi, M. Amin; Brennan, Michael J. [UNESP]; IOP (Iop Publishing Ltd, 2016)
The aim of this paper is to examine the effect of asymmetry in the force-deflection characteristics of an insect flight mechanism on its nonlinear dynamics. An improved simplified model for insect flight mechanism is suggested and numerical methods are used to study its dynamics. The range at which the mechanism may operate is identified. The asymmetry can lead to differences in the velocity in the upward and downward movements which can be beneficial for the insect flight.